On the construction of the object in sociology: Bourdieusian categories to understand “sustainability adherents” (Educação e Pesquisa, 2022)
The paper addresses the issue of the construction of the sociological object anchored on a research about the appropriation of the idea of “sustainability” by agents engaged in the economic field. The main objective is to discuss - based on an ongoing research - about the relevance of Pierre Bourdieu’s contributions with regard to the methods of constructing, designing and operationalizing social research. The paper also intends to minimize thelack of publications that directly explain sociological specificities: from the rupture with common sense to the analytical developments derived from the investigation process. The research, started in 2015, has some analytical dimensions that emphasize the sociogenesis of the phenomenon of the so-called corporate sustainability, the formation of an elite of top managers adherents and the correspondent educational processes in business schools. First,the paper discusses the need to make a rupture with the preconceptions that base common sense on corporate sustainability and the path taken to the guiding research question. Then, it highlights the sociological categories that facilitated the operationalization of the first two research axes: the sociogenetic analysis and the prosopography of an elite of adherents. Finally, the current stages of the research are presented, whose focus is on thedimension of the social reproduction of adherents of corporate sustainability, which occurs mainly through management education in business schools.